EDUKASI DAN PENCEGAHAN HIPERTENSI PADA LANSIA DENGAN SENAM AEROBIC LOW IMPACT - Nugraha, Adhelia Fitra; Putri, Agresia Monika; Utomo, Derik Cahyo; Aziz A.I, M Nawfal; Ulfah, Putri Nuriya; Setiawan, Cahyo; Ramadhani, Alinda Nur (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Hypertension is a leading risk factor for cardiovascular diseases, affecting approximately 10% of the world’s population according to WHO (2020). In elderly populations, lifestyle factors such as poor diet and lack of physical activity significantly contribute to the prevalence of hypertension. This research focuses on addressing this issue by utilizing low-impact aerobic exercise as an intervention to educate and prevent hypertension among the elderly. determine the effectiveness of this intervention in reducing hypertension risk and increasing awareness. A pre-experimental research design with a pre-test and post-test approach was employed, involving a group of elderly participants who were provided with hypertension education and guided through a low-impact aerobic exercise program. The findings revealed a notable increase in participants’ knowledge of hypertension and its risk factors, as well as a positive effect on their physical well-being. After the intervention, participants demonstrated improved understanding of hypertension management through lifestyle modifications. suggest that integrating low-impact aerobic exercise into elderly health programs can play a significant role in hypertension prevention. The study that this type of intervention is both practical and effective in improving knowledge and reducing hypertension risks among elderly populations.